Science 2.0: contribution of university libraries - Merlo-Vega, José-Antonio (Anuario ThinkEPI, 2011)
The report of the Spanish Network of University Libraries (Rebiun) "Science 2.0: implementation of the social web to research" is discussed, and the main websites that allow scientists to cooperate or share in the three facets of research, resources and results are listed. University libraries should play an active role in the 2.0 environment to serve scientific research.